2014
DOI: 10.1002/jso.23758
|View full text |Cite
|
Sign up to set email alerts
|

Frozen section examination may facilitate reconstructive surgery for mid and low rectal cancer

Abstract: FS examination may help determine free distal margin and consequently, in selected cases, may facilitate a restorative procedure in patients with low rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In patients with upper rectal and rectosigmoid tumors, the intraoperative assessment of margins with frozen section is not routinely necessary as adequate margins can be achieved while more easily restoring intestinal continuity. Frozen section has a sensitivity and specificity of 83% and 98%, respectively, for rectal cancer and a frozen section negative margin of >5 mm correlates well with negative margin on final surgical pathology . Newer technology such as multiphoton microscopy is being evaluated as a real time assessment of surgical margins without the need for tissue processing .…”
Section: Intraoperative Assessment Of Marginsmentioning
confidence: 99%
“…In patients with upper rectal and rectosigmoid tumors, the intraoperative assessment of margins with frozen section is not routinely necessary as adequate margins can be achieved while more easily restoring intestinal continuity. Frozen section has a sensitivity and specificity of 83% and 98%, respectively, for rectal cancer and a frozen section negative margin of >5 mm correlates well with negative margin on final surgical pathology . Newer technology such as multiphoton microscopy is being evaluated as a real time assessment of surgical margins without the need for tissue processing .…”
Section: Intraoperative Assessment Of Marginsmentioning
confidence: 99%
“…It has been suggested that intraoperative frozen section of surgical specimens may provide an accurate diagnosis to guide the selection of surgical procedures (18). In the current case, histopathological examination of the surgical specimen was performed postoperatively, therefore further strategic planning of the surgical operation and intraoperative management of the patient was straightforward.…”
Section: Discussionmentioning
confidence: 90%
“…Several methods have been developed for intra-operative colorectal tumor localization, such as barium enemas [4,5], frozen sections [6,7], pre-operative endoscopic tattooing or clip placement [8][9][10][11][12][13][14], intra-operative endoscopy [15], fluorescence guidance [16][17][18], and surgical navigation technology [19,20]. However, these techniques all have certain drawbacks, including radiation exposure, a long duration, non-optimal accuracy, complexity, and the need for special instruments or technical support.…”
Section: Introductionmentioning
confidence: 99%